Isotope and Geochemistry Characterization of Hot Springs and Cold Springs of Sembalun – Rinjani Area, East Lombok, West Nusa Tenggara – Indonesia - Satrio Satrio; Rasi Prasetio; Boy Yoseph Cahya Sunan Sakti Syah Alam; Teuku Yan Waliyana Muda Iskandarsyah; Faizal Muhammadsyah; Mohamad Sapari Dwi Hadian; Hendarmawan Hendarmawan (Universitas Gadjah Mada, 2020)
The presence of several hot springs in Sembalun – Rinjani, East Lombok, West Nusa Tenggara is an indicator of geothermal potential in the area. This study aims to determine the characteristics of hot springs and cold springs and also the geothermal potential in Sembalun – Rinjani area using isotopes and geochemistry methods. The result of d18O and d2H stable isotopes analysis shows that most of the hot springs are meteoric water. Except for Kalak hot spring, other hot springs are a mixing product of meteoric water and andesitic water, with meteoric water composition between 64 to 87%. While 14C radioisotope suggests that the age of hot springs in the Sembalun area is about 10,000–12,000 years BP, the surrounding cold springs are mostly Modern except Jorong cold spring. The results of gas analysis (He, Ar, and Ne) also suggest the same origin of geothermal fluid, i.e., meteoric water origin. Based on chemical composition, Kalak hot spring is plotted as sulfate type water, while Sebau hot spring is plotted near mature water composition but not representing reservoir fluid due to its relatively low temperature and high Mg content. Na/K geothermometer calculation from Sembalun area shows that subsurface temperature is varied between 111-161 °C, while from Rinjani hot springs indicates higher subsurface temperature, i.e., 250-260 °C. It is estimated that reservoir fluid has high TDS with chloride content up to 4000 mg/L.